Conceptual and Aesthetic Transformation in “Baris Dance” Painting by Anak Agung Gede Sobrat after the influence of Rudolf Bonnet and Wallter Spies - Paramarta Krisna Prabu, A.A. Gede Bayu (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2026)
This research aims to analyze the transformation of concepts and aesthetic forms in the “Baris Dance” painting by Anak Agung Gede Sobrat following the influence of Western artists, namely Wallter Spies and Rudolf Bonnet. Anak Agung Gede Sobrat, known as Sobrat, is recognized as one of the pioneers of modern Balinese painting, particularly within the Ubud style, which experienced significant development through interaction with Western culture during the colonial period. This research employs a qualitative method with a descriptive-analytical approach. The aesthetic analysis is conducted using the theory of Monroe Beardsley, which emphasizes three main aspects: unity, complexity, and intensity. Meanwhile, the theory of cultural change proposed by Poerwanto is used to examine the processes of cultural transformation resulting from external influences, particularly diffusion and acculturation between Western and Balinese artistic traditions. The results indicate that the “Baris Dance” painting by Anak Agung Gede Sobrat demonstrates strong aesthetic qualities through harmonious compositional unity, intricate visual complexity, and expressive intensity. Furthermore, significant transformations are identified in terms of theme, technique, and media usage. The thematic focus, which initially centered on epic narratives such as wayang stories, evolved into representations of Balinese social and cultural life. The application of coloring techniques and materials also reflects Western influence, while still preserving traditional Balinese values. In conclusion, the “Baris Dance” painting represents a synthesis of local tradition and Western influence, resulting in a new aesthetic form within the development of modern Balinese painting, particularly in the Ubud style.